-3(w-1)=-6w-18

Simple and best practice solution for -3(w-1)=-6w-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(w-1)=-6w-18 equation:



-3(w-1)=-6w-18
We move all terms to the left:
-3(w-1)-(-6w-18)=0
We multiply parentheses
-3w-(-6w-18)+3=0
We get rid of parentheses
-3w+6w+18+3=0
We add all the numbers together, and all the variables
3w+21=0
We move all terms containing w to the left, all other terms to the right
3w=-21
w=-21/3
w=-7

See similar equations:

| -x(2x-8)-5x=0 | | -8u-4=4u+12 | | 8^2+32x+30=0 | | -5y-19=-3(y+1) | | x/6=12/x | | 9(y-2)=2y-46 | | 4c+7c=$1.50 | | r=99/3 | | -3x+20=-60x-20 | | 3/4x=1/8x-6=15 | | (y-6/y)-6/y=(y+6)/(y-6) | | 5-4x=8x+6 | | 3x=6 7 | | F(z)=2z-8/7z+2 | | x^2-12x+67=0 | | 0.3=0.5^x | | 3x-3+22=4x-1+9x | | 3.6=1.2r | | -3(k-1)=3(k+1)-48 | | 4x-2(2-3x)=4(x-4)-6 | | 8y-4×=12 | | 4(k-4)-3(k+1)-14=-26 | | X+x+6=20-x | | x^2+10x-24=-9 | | 3x-3+22=5x-1+8x | | 25-3x=5+x | | 12P=3b^2 | | -5(3w+1)-w=43 | | 0=28x-3x^2 | | n+7/9=17/18 | | 9k×96=98;K= | | -500x(2x-9)=0 |

Equations solver categories